GATA3 mRNA expression, but not mutation, associates with longer progression-free survival in ER-positive breast cancer patients treated with first-line tamoxifen for recurrent disease. Issue 1 (28th June 2016) - Liu, Jingjing; Prager–van der Smissen, Wendy J.C.; Look, Maxime P.; Sieuwerts, Anieta M.; Smid, Marcel; Meijer–van Gelder, Marion E.; Foekens, John A.; Hollestelle, Antoinette; Martens, John W.M.
Highlights: GATA3 mutations were identified among 14% of ER-positive breast cancer patients. GATA3 mutations did not predict the response to tamoxifen for advanced disease. GATA3 mutations associate with an increased expression of GATA3 mRNA. GATA3 mRNA level is an independent predictor of longer PFS during tamoxifen therapy. Other mechanisms, besides GATA3 mutations, exist that underlie high GATA3 levels. Abstract: In breast cancer, GATA3 mutations have been associated with a favorable prognosis and the response to neoadjuvant aromatase inhibitor treatment. Therefore, we investigated whether GATA3 mutations predict the outcome of tamoxifen treatment in the advanced setting. In a retrospective study consisting of 235 hormone-naive patients with ER-positive breast cancer who received tamoxifen as first-line treatment for recurrent disease, GATA3 mutations (in 14.0% of patients) did not significantly associate with either the overall response rate (ORR) or with the length of progression-free survival (PFS) after the start of tamoxifen therapy. Interestingly, among 148 patients for whom both mutation and mRNA expression data were available, GATA3 mutations associated with an increased expression of GATA3 . However, only 23.7% of GATA3 high tumors had a mutation. Evaluation of the clinical significance of GATA3 mRNA revealed that it was associated with prolonged PFS, but not with the ORR, also in multivariate analysis. Thus, GATA3 mRNA expression, but not GATA3 mutation, is an independent predictor of prolonged PFS in ER-positive breast cancer patients who received first-line tamoxifen for recurrent disease. Besides GATA3 mutation, other mechanisms must exist that underlie increased GATA3 levels.